The impact of rs6198 genotyping of glucocorticoid b-receptor gene in sepsis - Antonios Arapis; Georgia Damoraki; Dimitra Papatheodossiou; Stelios Apostolidis; Evangelos J Giamarellos Bourboulis (Journal of Global Antimicrobial Resistance)
BACKGROUND: Glucocorticosteroids (GCs) are used for the treatment of sepsis, while their role is mediated exclusively by the glucocorticoid receptor (GR) and its gene NR3C1. The rs6198 single-nucleotide polymorphism (SNP), localized in exon 9β of the NR3C1, has been shown to increase GC sensitivity. Acute Respiratory Disease Syndrome (ARDS) is an acute form of respiratory failure, and it is usually treated with the use of GCs. AIM: We aimed to determine outcomes of sepsis patients with/without ARDS in relation to the carriage of the rs6198 single nucleotide polymorphisms (SNPs) METHODS: DNA was isolated from whole blood of adults with septic shock treated with GCs; it was amplified by PCR. The rs6198 genotyping was done by Sanger sequencing. RESULTS: A total of 361 patients was studied; 198 were AA homozygous for the major frequency A allele, 134 were AG heterozygotes and 29 were GG homozygotes for the minor frequency allele. 28-day mortality was 46% (n=91), 41,8% (n=56) and 34,5% (n=10) respectively. Among these patients, 75,3% (n=149), 73.1% (n=98) and 65.5% (n=19) presented with ARDS. 28-day mortality in the absence of ARDS was 54.5% (n=18), 42.4% (n=14) and 3% (n=1). CONCLUSIONS: Presence of the GG genotype is associated with the final outcome of sepsis among patients with sepsis in need of GG without ARDS.